"We may be pirates, but we are not protesters": Identity in the Sea Shepherd Conservation Society. Issue 5 (18th February 2013) - Stuart, Avelie; Thomas, Emma F.; Donaghue, Ngaire; Russell, Adam
<x xml:space="preserve">Abstract</x> Radical activist organizations face the complex task of managing their identity so as to draw political attention but also to appear legitimate and thus gain public support. In this article we develop a picture of the identities of Sea Shepherd Conservation Society (SSCS) members, a group mostly known for their direct action against whaling, via a thematic analysis of material from the SSCS website and interviews with SSCS members. In online commentary, founder Captain Paul Watson establishes several deliberately paradoxical notions of who the Sea Shepherds are. We relate these identity statements to interviews with core activists to examine how they manage the identity conflicts resulting from the group identity, such as being seen as "pirates" and "hard lined vegans." We found that SSCS positions themselves as a diverse and unstructured organization, yet distinctively passionate and willing to take action where others will not. The implications of this research are discussed in relation to the importance of understanding the constraints and conflicts around political activist identities.